Improving patient outcomes in psoriasis: strategies to ensure treatment adherence - Yélamos O; Ros S; Puig L (Dove Medical Press, 2015)
Oriol Yélamos, Sandra Ros, Lluís Puig Department of Dermatology, Hospital de la Santa Creu i Sant Pau – Universitat Autònoma de Barcelona, Barcelona, Catalonia, Spain Abstract: Psoriasis is a frequent inflammatory disease with a chronic and relapsing course. Therefore, patients with psoriasis are likely to undergo different treatments for long periods of time. Traditionally, therapies used in psoriasis have been associated with poor levels of adherence due to the complexity of the regimens and the poor results obtained with the topical therapies. These poor outcomes are associated with high levels of frustration and anxiety, which decrease adherence and worsen the disease. With the recent introduction of highly efficacious biologic therapies, patients can achieve very good and prolonged responses. However, most patients with psoriasis have mild disease and may be treated with skin-directed therapies. Therefore, it is important to develop strategies to improve adherence in order to achieve better outcomes, and to improve the overall quality of life. Hence, acknowledging the causes of nonadherence is crucial for implementing these strategies. In this summary, we review the causes of nonadherence, and we provide behavioral strategies in order to improve adherence and, ultimately, the outcome of patients with psoriasis. Keywords: psoriasis, adherence, outcome, drug therapy, psychotherapy